Bias Gender Pendidikan Islam Indonesia : Gender Bias In Indonesian Islamic Education - HM. Syamsudini (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2015)
In the context of Indonesian Muslim society, male dominance is still so strong that contextualizing the spirit of non-discrimination in Islam becomes inappropriate when confronted with reality. The majority of Muslim communities generally believe that it is best to keep men and women in separate spaces, and that the intrusion of women into male domains will cause “chaos” that will destroy the basic order in all matters. The difficulty of access for women to obtain education is undeniably a legacy of Islamic religious traditions that were influenced by patriarchal bias when fiqh law was codified. Although the tradition itself is not always supported by the Qur'an, it has been and will continue to be influential in determining the opportunities available to women. Thus, the fact that education for women is minimal has become a common phenomenon in the Islamic world. Dalam konteks masyarakat muslim Indonesia dominasi laki-laki masih demikian kuat, sehingga kontekstualisasi semangat nondiskriminasi dalam Islam menjadi tidak sesuai ketika dihadapkan dengan realitas. Mayoritas masyarakat muslim pada umumnya percaya bahwa paling baik menjaga laki-laki dan perempuan dalam ruang yang ditetapkan terpisah, dan bahwa penerobosan perempuan ke dalam wilayah laki-laki akan menyebabkan